Gaya Bahasa Sya’ir أيا من يدعي الفهم Karya Al-Hariri yang Dilantunkan oleh Syeikh Mishary Rasyid (Kajian Stilistika) - Anisa; Syihabuddin; Maman Abdurrahman (Uktub: Journal of Arabic Studies, 2024)
The poem "أيا من يدعي الفهم" (O You Who Claims Understanding), created by Abu Muhammad Alqosim bin Ali al-Hariri, and later recited by the renowned qari’ Sheikh Mishary Rasyid, provoked various reactions among internet users. Hence, this research aims to analyze the stylistic elements of this poem. Qualitative descriptive methods and content analysis were employed in this study, collecting data through observation, note-taking, and purposive sampling techniques. The findings indicate that the poetic style creates effects such as enhancing faith, self-reflection, satire, and emotional impact. These effects are constructed through the following aspects: (1) phonological aspects, including the harmony of the rhyme at the end of verses and the use of specific rhythmic patterns (shawamit infijariyah and shawait qashirah); (2) Morphological aspects dominated by fi’il madhi and fi’il mudhari’, sarcastically criticizing individuals for their reprehensible actions, and fi’il amr and nahyi for advice and conclusion in the poem; (3) Syntactic aspects involving repetition and ellipsis for reinforcing and expanding on the subjects of criticism; (4) Semantic aspects employing unusual word meanings to captivate the audience's attention; and (5) Imagery aspects creating beauty and coherence through the use of assonance, alliteration, epithets, euphemisms, sarcasm, cynicism, and cause-and-effect coherence. The implications suggest that this work could serve as an alternative form of contemporary preaching (dakwah) and remains relevant in literary works within a modern context.